2019
DOI: 10.3389/fpls.2019.01081
|View full text |Cite
|
Sign up to set email alerts
|

Mutation at Different Sites of Metal Transporter Gene OsNramp5 Affects Cd Accumulation and Related Agronomic Traits in Rice (Oryza sativa L.)

Abstract: OsNramp5 is a key gene involved in the control of the uptake of Cd, Mn, and other metal ions by rice root cells. The functional deficiency of this gene can significantly reduce the accumulation of Cd in rice grains, but the effects of its mutation on agronomic traits such as yield and quality have not been investigated comprehensively yet. In the present study, three Huanghuazhan-based OsNramp5 mutants [LCH1 (Low Cadmium Huanghuazhan 1), LCH2 (Low Cadmium Huanghuazhan 2), and LCH3 (Low Cadmium Huanghuazhan 3)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…Therefore, we speculate that it is on the other way in plants, and it is consistent with the result of the current study. In the present study, the phylogenetic tree showed that the intron length of Nramp transporter genes increased with evolution in plants, whereas the intron number of EIN family remained almost unchanged (4)(5)(6)(7)(8). Similarly, the number of motifs of the Nramp transporter genes also increased through evolution in general while the number of motifs of EIN family remained stable.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, we speculate that it is on the other way in plants, and it is consistent with the result of the current study. In the present study, the phylogenetic tree showed that the intron length of Nramp transporter genes increased with evolution in plants, whereas the intron number of EIN family remained almost unchanged (4)(5)(6)(7)(8). Similarly, the number of motifs of the Nramp transporter genes also increased through evolution in general while the number of motifs of EIN family remained stable.…”
Section: Discussionsupporting
confidence: 55%
“…Natural resistance-associated macrophage proteins (Nramps), which comprise a highly conserved gene family across all species, from bacteria to humans, and are identified as an integral membrane protein family, are critical proton/metal transporters in plants [1][2][3][4]. The genes of the Nramp transporter family play important roles in the transport of ions, such as Cd, Fe, Mn, and Zn [5][6][7][8][9][10]. In Arabidopsis thaliana, AtNramp1 is located in the plasma membrane and is identified as an Fe, Mn, and Cd transporter [11,12], whereas AtNramp2 is located in endomembrane and acts in the distribution of Mn between intracellular organelles [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Genomics approaches' advancement enhances the identification of multiple genes involved in phytoremediation, plant stress tolerance, and transport of heavy metals, such as DNA mismatch repair (MMR) in a soybean cultivar [250], targeted induced local lesions in genomes (TILLING) in rapeseed [8], clustered regularly interspaced short palindromic repeats (CRISPER/Cas9) in rice [251], and genome-wide association studies (GWAS) in rapeseed [252,253].…”
Section: Genomicsmentioning
confidence: 99%
“…CRISPER/Cas9 technology was used to obtain three mutants (LCH1, LCH2, and LCH3) of the OSNramp5 gene from rice that were involved in the uptake of Cd and other metal ions from root cells [ 251 ]. Tang et al [ 256 ] used the CRISPER/Cas9 system in the rice indica gene OsNramp5 to reduce Cd accumulation in rice for food safety, and demonstrated a 0.05 mg kg −1 decrease in the Cd concentration whereas the plant yield was not affected.…”
Section: Omics Approaches For Cadmium Phytoremediationmentioning
confidence: 99%
“…Such work has particularly focused on genes that encode either transporters, such as natural resistanceassociated macrophage proteins (NRAMPs) [18][19][20][21][22][23][24][25] , which mediate the entry of Cd from the rhizosphere, or those such as heavy metal ATPases (HMAs) [26][27][28][29][30][31][32] , which determine the deposition of Cd in vacuoles or its translocation in the plant. Significant findings include (i) that the level of NRAMP5 in rice may be linked to the higher uptake of Cd in this species than in maize 21 , (ii) combining knockout of one homeologous HMA4 gene (nonsense mutation) and reduction of the other (missense mutation) reduced Cd levels in tobacco, while maintaining plant vigour 27 , and (iii) the identification in wheat of HMA3 variants linked to reduced Cd accumulation 26 .…”
Section: Introductionmentioning
confidence: 99%